Safety in food handling. - 4 0 16; 5 (Australia : Video Education Australasia)
This pprogram looks at practical steps to keep food safe from contaminants which often cause serious illness. It is especially relevant to those who work in the food service industry, however the principles apply to anyone who handles food on a regular basis. As a teaching tool, it divides netaly into the following chapters: The Enemy - micro-organisms that cause food poisoning; Enemy tactics - cross-contamination of food; Taking action - practising safe food handling. With explanation of the issues, clear demonstrations, graphics and handy tips along the way.
Keywords: 2 -- 0; 6; Food handling.;Food contamination. -- 20; 20; 2